2016
DOI: 10.1016/j.knosys.2016.05.010
|View full text |Cite
|
Sign up to set email alerts
|

A framework for diversifying recommendation lists by user interest expansion

Abstract: Recommender systems have been widely used to discover users’ preferences and recommend interesting items to users during this age of information load. Researchers in the field of recommender systems have realized that the quality of a top-N recommendation list involves not only relevance but also diversity. Most traditional recommendation algorithms are difficult to generate a diverse item list that can cover most of his/her interests for each user, since they mainly focus on predicting accurate items similar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…The insights may help to design better result ranking strategies and evaluation metrics. Besides, diversity is also enforced in other applications such as image recommendation [32], movie recommendation [33], and general purpose recommendation tasks [34]. Similar as the retrieval task, it has been shown that more diversity can bring user with better experience.…”
Section: Visual-semantic Retrievalmentioning
confidence: 99%
“…The insights may help to design better result ranking strategies and evaluation metrics. Besides, diversity is also enforced in other applications such as image recommendation [32], movie recommendation [33], and general purpose recommendation tasks [34]. Similar as the retrieval task, it has been shown that more diversity can bring user with better experience.…”
Section: Visual-semantic Retrievalmentioning
confidence: 99%
“…While personalized recommendation diversity reduces accuracy to a certain degree but improves users' subjective evaluation of the recommendation system [11]. Some "dark information" that users may be interested in has been ignored, thus recommendation are unable to meet their real needs [12].…”
Section: Personalized Recommendation Diversitymentioning
confidence: 99%
“…Most existing works evaluate the capability of a RS to diversify recommendations on two criteria -individual diversity (ID) [19] and aggregate diversity (AD) [16]. Individual diversity [20] refers to the breadth or range of (varied) items suggested to a given user.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to exploiting the available rating values, we also use item metadata (in our case movie genres) to explicitly enforce desired diversifying criteria. To the best of our knowledge, there are very few works in the past [19,36,38] which exploit available secondary data (metadata) to establish diversity-accuracy tradeoff. In [19], authors use user tagging (user metadata) information to develop expansion strategy for user interest and suggest diversified items.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation